Associations between Mycoplasma genitalium, Chlamydia trachomatis, and pelvic inflammatory disease. Issue 2 (1st April 2003) - Simms, I; Eastick, K; Mallinson, H; Thomas, K; Gokhale, R; Hay, P; Herring, A; Rogers, P A
Abstract : Objective: To evaluate the association between Mycoplasma genitalium, Chlamydia trachomatis, and pelvic inflammatory disease (PID) Methods: A case-control methodology was used. Swab eluates were processed using the QIAamp DNA mini kit. Polymerase chain reaction (PCR) for M genitalium was carried out using a real time in-house 16S based assay. An endocervical swab was taken and tested for the presence of C trachomatis (ligase chain reaction, Abbott Laboratories), and a high vaginal swab was taken and tested for the presence of Neisseria gonorrhoeae and bacterial vaginosis. Results: Of the PID cases 13% (6/45) had evidence of M genitalium infection compared to none of the controls (0/37); 27% (12/45) of the cases had C trachomatis infection compared to none of the controls; and 16% (7/45) of cases only had serological evidence of C trachomatis infection compared to 5% (2/37) of controls. Cases were more likely to present with M genitalium and/or C trachomatis than controls (p<0.001). Conclusions: This study indicates that there may be an association between M genitalium and PID, and that this relation is largely independent of C trachomatis . Future studies need to investigate the pathological basis of the relation between M genitalium and PID using samples from women with PID diagnosed using laparoscopy and endometrial biopsy. Little is known about the epidemiology of M genitalium : large scale epidemiological investigations are needed to determine the prevalence, incidence, and factors associated with this emerging infection.